Preoperative prediction and prevention of intraoperative acute liver failure after major liver resection for metastatic colorectal cancer - A. D. Kaprin; D. V. Sidorov; N. A. Rubtsova; A. V. Leont’ev; M. V. Lozhkin; L. O. Petrov; T. N. Lazutina; N. A. Grishin; I. V. Pylova; A. G. Isaeva (Тазовая хирургия и онкология, 2016)
Objective: improve the results of treatment of patients with metastatic cancer of liver by reducing the risk of post-resection liver failure based on the assessment of liver functional reserve.Materials and methods. The study included 2 independent samples of patients underwent surgery for liver metastases in the department of abdominal oncology at the P. A. Herzen Moscow Oncological Research Institute. Group 1 included 47 patients: in addition to the standard treatment algorithm they underwent 13C methacetin breath test and dynamic scintigraphy of liver in the preoperative stage. Patients from the group 2 (n = 30) underwent standard clinical and laboratory examination, without preoperative evaluation of liver functional reserves; the level of total bilirubin, albumin and prothrombin time showed no decrease in liver function. Post-resection liver failure was established based on 50/50 criterion when evaluated on the 5th postoperative day.Results. The analysis of operational characteristics of functional tests showed absolute sensitivity of 13C methacetin breath test (SE ≥ 100 %) and negative predictive value (–VP ≥ 100 %) in case of integrated application of 2 diagnostic methods. An incidence of post-resection acute liver failure in the study group was significantly 2.2-fold lower than in the control group – 10.6 % and 23.3 %, respectively (p < 0.001).Conclusion. Combination of preoperative dynamic scintigraphy of liver with 13C methacetin breath test allows to perform comprehensive assessment of liver functional reserves, and it can greatly improve preoperative assessment and postoperative results of anatomic resections in patients with liver metastases.